AB0652 Early organ involvement, survival and causes of death in an unselected cohort of dutch patients with systemic sclerosis. (15th June 2017) - Vonk, M; Hombergh, W van den; Knaapen, H; Hoogen, F van den; Fransen, J
Abstract : Background: Systemic sclerosis (SSc) patients are at risk for organ involvement and premature death. The occurrence of organ involvement that is reported differs widely between various long term cohort studies; ILD 25–90%, PAH 8–32%, CI 5–30%, and SRC 4–12%. Differences in findings also apply to survival, the 5- and 10-year survival rates between studies vary from 80% to 90% and from 60% to 85% respectively (1–3). Objectives: To assess the occurrence of organ involvement and death in a large, unselected cohort of Dutch SSc patients at the moment of diagnosis and during 5 years of follow-up, stratified by disease subtype and auto-antibodies. Methods: Up to 2015, 690 SSc patients were included in the Nijmegen SSc cohort. Occurrence of interstitial lung disease (ILD), pulmonary arterial hypertension (PAH), cardiac involvement (CI), scleroderma renal crisis (SRC) and occurrence of death were determined using survival analysis, stratified by disease subtype (limited cutaneous SSc and diffuse cutaneous SSc) and auto-antibodies (ACA, ATA, anti-RNP). Results: Organ involvement was already present at SSc diagnosis in 32% of patients. In 25%, organ involvement developed during follow-up, mostly ILD (22%). Significant differences between lcSSc and dcSSc were found in SRC at baseline and ILD, PAH and SRC during follow-up. Between the autoantibody subgroups, the occurrence of ILD, PAH and SRC at baseline and ILD during follow-up differed. There were no differences in survival between subtypes and auto-antibodies. The overall 5-year survival rate was 89%. Patients without organ involvement at SSc diagnosis had a better 5-year survival rate than patients with organ involvement at SSc diagnosis: 95% versus 73% respectively (p<0.001). (figure 1) Conclusions: In many SSc patients, organ involvement is already present at diagnosis or develops in the first 5 years after diagnosis. Survival is significantly worse in patients who already have involvement at the moment of SSc diagnosis. References: Muangchan C, Canadian Scleroderma Research G, Baron M, Pope J. The 15% rule in scleroderma: the frequency of severe organ complications in systemic sclerosis. A systematic review. The Journal of rheumatology. 2013;40(9):1545–56. Vonk MC, Broers BM, Heijdra YF, Ton E, Snijders R, van Dijk AP, et al. Systemic sclerosis and its pulmonary complications in the Netherlands An epidemiological study. AnnRheumDis. 2008. Nihtyanova SI, Schreiber BE, Ong VH, Rosenberg D, Moinzadeh P, Coghlan JG, et al. Prediction of pulmonary complications and long-term survival in systemic sclerosis. Arthritis & rheumatology. 2014;66(6):1625–35. Disclosure of Interest: None declared